A mindfulness‐based intervention for caregivers of allogeneic hematopoietic stem cell transplant patients: Pilot results. Issue 5 (20th February 2020) - Vinci, Christine; Pidala, Joseph; Lau, Penny; Reblin, Maija; Jim, Heather
Abstract: Despite high levels of stress, there are few empirically supported stress management interventions for caregivers of allogeneic hematopoietic stem cell transplant (HCT) cancer patients. This study examined the feasibility, acceptability, and various stress‐related outcomes from pre‐ to post‐treatment of a pilot, single‐arm trial of a 6‐week mindfulness‐based intervention (FOCUS) for stress management. Caregivers ( N = 21; 76% female; mean age = 57.43) were enrolled prior to patient transplant and received FOCUS during the first 90 days post‐transplant. Findings indicated that FOCUS was highly feasible and acceptable (e.g., 71% attended at least four of six sessions; 100% reported using the skills learned at follow‐up; high treatment engagement). Significant increases in mindfulness, post‐traumatic growth, and general mental health were observed, along with significant decreases in negative affect (all p s < .05).